The political system of Russia between democratization and authoritarianism - Bujwid-Kurek, Ewa; Susolia, Artem (Sociološki pregled, 2023)
The main research objective of this article was to assess the nature of the democratization of Russia’s political system in the period 1985-2000. The authors analyze the selected period of the transformation in Russia based on the concept of S. Huntington, considered the most adequate theory of democratization. The authors attempted to answer following questions: what changes occurred during the “Perestroika” process initiated by M. Gorbachev - unsuccessful liberalization for Soviet Russia and “started” the Third wave of democratization of the Russian Federation; secondly, what was the specificity of the democratization of the political system during the presidency of Boris Yeltsin; and lastly, when the retreat from democratization began in Russia. This analysis seems quite sensible due to the fact that it can explain the reasons for the retreat from democracy during the presidency of V. Putin and the construction of an authoritarian state in Russia in the 21st century. In order to verify the hypotheses and answer the research questions, the classic method for the social sciences was chosen (the decision-making, systemic, and case study methods).
Keywords: Russia; democratization; Samuel Huntington’s “waves of democratization”